Modelling the Firm in its Market and Organizational Environment: Methodologies for Studying Corporate Social Responsibility - Crouch, Colin (Organization studies, 2006)
The study of corporate social responsibility (CSR) can best be mainstreamed within the wider social science literature if it is defined as firms voluntarily assuming responsibility for their externalities, thereby setting the puzzle of how this can be reconciled with the maximization of shareholder value as the central challenge of the subject. Means of resolving the puzzle require modelling the firm interacting with its environment as both a market actor and as an organization, and in particular through the interaction between these two. Such an approach has no need of a separate concept of ‘stakeholders’. The analysis develops through the firm's relations with actual and potential political action (raising the separate issue of corporate citizenship), and the tastes of consumers, investors and employees—the last raising interesting implications for principal–agent theory.